Banana trunk for zinc (ii) removal - Yong, Lit Yuan (School of Materials Engineering, University Malaysia Perlis, 2016)
The purpose of this study is to investigate the effectiveness of agro-waste, namely banana trunk fibres act as an adsorbent for zinc ion removal in aqueous solution. The surface morphology and the functional group exist on banana trunk are determine by using Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) respectively. Atomic Absorption Spectroscopy (AAS) is use to determine the zinc (II) ions concentration. The effect of pH value, contact time, adsorbent dosage and initial metal ions concentration were studied at ambient temperature, 25 C. The optimum pH value, contact time, adsorbent dosage and initial metal ions concentration obtained in this study were pH 8, 120 minutes, 0.5 gram and 10 mg/L (ppm) respectively. Langmuir, Freundlich and BET isotherms were used to determine the equilibrium state for heavy metal ions adsorption experiments. Freundlich isotherm consist of R2 = 0.9356 and maximum adsorption capacity, Kf = 0.175 mg/g has the better fit if compare to Langmuir and BET isotherms. It is conclude that banana trunk has the potential for heavy metal removal from aqueous solution.